2011
DOI: 10.1089/scd.2010.0209
|View full text |Cite
|
Sign up to set email alerts
|

Dual Roles of Oct4 in the Maintenance of Mouse P19 Embryonal Carcinoma Cells: As Negative Regulator of Wnt/β-Catenin Signaling and Competence Provider for Brachyury Induction

Abstract: Transcription factor Oct4 is expressed in pluripotent cell lineages during mouse development, namely in inner cell mass (ICM), primitive ectoderm, and primordial germ cells (PGC). Functional studies have revealed that Oct4 is essential for the maintenance of pluripotency in ICM and for the survival of PGC. However, the function of Oct4 in the primitive ectoderm has not been fully explored. In this study, we investigated the role of Oct4 in mouse P19 embryonal carcinoma (EC) cells, which exhibit molecular and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…The b-cateninOct4 interaction appears to be evolutionarily conserved, and Xenopus Oct4 homologs (Oct-60 and Oct-25) inhibited transcription of bcatenin-regulated genes during germ layer specification (Cao et al 2007;Abu-Remaileh et al 2010). An essentially identical effect of Oct4 inhibiting b-catenin stimulation of TOPFlash activity also occurred in the P19 embryoid carcinoma cell line (Marikawa et al 2011). This Oct4 effect in P19 cells was shown to be cellautonomous; however, overexpression of an Oct4-engrailed repressor fusion protein stimulated TOPFlash, whereas an Oct4-VP16 transactivator fusion protein inhibited TOPFlash activity.…”
Section: Potential Tcf-independent Mechanismsmentioning
confidence: 61%
See 1 more Smart Citation
“…The b-cateninOct4 interaction appears to be evolutionarily conserved, and Xenopus Oct4 homologs (Oct-60 and Oct-25) inhibited transcription of bcatenin-regulated genes during germ layer specification (Cao et al 2007;Abu-Remaileh et al 2010). An essentially identical effect of Oct4 inhibiting b-catenin stimulation of TOPFlash activity also occurred in the P19 embryoid carcinoma cell line (Marikawa et al 2011). This Oct4 effect in P19 cells was shown to be cellautonomous; however, overexpression of an Oct4-engrailed repressor fusion protein stimulated TOPFlash, whereas an Oct4-VP16 transactivator fusion protein inhibited TOPFlash activity.…”
Section: Potential Tcf-independent Mechanismsmentioning
confidence: 61%
“…The Oct4-mediated decrease in b-catenin was blocked by mutating GSK3-phosphorylation sites in b-catenin, by inhibiting the proteasome with MG132, or by mutating APC (Abu-Remaileh et al 2010). In P19 cells, knocking down Oct4 stimulated several genes (Sp5, Wnt3, and Eomes), and this effect was significantly reduced by b-catenin shRNA (Marikawa et al 2011). Taken together, these results were interpreted to suggest that b-catenin stimulates differentiation of mESC, and Oct4 promotes self-renewal by inhibiting b-catenin's pro-differentiation effect.…”
Section: Potential Tcf-independent Mechanismsmentioning
confidence: 99%
“…A reciprocal interaction is possible, and Oct4 might be the reason for the inability of transcriptionally competent β-catenin to access the cytosol under self-renewal conditions: in the cadherin-based complex, Oct4 might block the release of the transcriptionally competent form of β-catenin. In this regard, there is evidence that Oct4 can antagonize the transcriptional activity of β-catenin (Anton et al, 2007; Marikawa et al, 2011), and, during differentiation, the activation of β-catenin reporters is concomitant with decreases in Oct4 and cadherin.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the Brachyury was still substantially up-regulated by pt-β-catenin even when Tcf3 was overexpressed. We previously demonstrated that a pluripotency regulator Oct4 acts as a competence factor for Brachyury (Marikawa et al, 2011). However, the expression level of Oct4 was unaffected by the overexpression of Nkx1-2, suggesting that Oct4 and Nkx1-2 function as competence factors through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%